E-GOVERNMENT IN LEBANON - Kayrouz, Akl; Atala, Issam (European Scientific Journal, ESJ, 2014)
Technological inventions stand beyond limits in applications to promote and sustain good governance, as man travels in open space, in search and discovery of the mysteries of the galaxies. In contrast, man in most developing countries still relies upon the primitive instinct reflected in thought, behavior, and culture of violence. Good governance is enhanced by technological discoveries to promote constructive communication, facilitate transactions, keep accurate records, provide better public services, and combat corruption. It is the key factor to promote governance transparency, managerial effectiveness and sustain development. The presence of good governance will help countries fight violence and corruption by spreading a sense of equity and utilitarianism. This research focuses upon collecting data from the developing country of Lebanon, in the MENA region, where most official and public transactions are still carried out, handwritten, in ledgers and endless bureaucratic tapes. The authors aim to collect and analyze the actual data, for its heartbreaking, that in the 21st century humans are still living in the swampy darkness of corruption and backwardness. The hypothesis of this research aims at highlighting the importance and values, produced by the application of e-government to help sustain the country’s development.